Percutaneous Device Closure of Ductus Arteriosus in a 1.3Kg Baby - Ara, Andaleeb; Mahmood, Amjad; Akhtar, Khurram; Imtiaz, Sana; Ahmed, Tufail; Farhan, Mohammad Asad (Pakistan Armed Forces Medical Journal, 2022)
Patent ductus arteriosus (PDA) is a common cardiac anomaly making 5%-10 % of all congenital heart diseases. The incidence increases in premature, very low birth weight neonates. Transcatheter closure is a standard procedure for treating PDA.However, in pre-term and very low birth weight neonates it presents special problems thus becoming a limitation in performing the procedure. This case report describes a PDA closure in a 1.3 Kg infant in Armed Forces Institute of Cardiology,Rawalpindi.